2013
DOI: 10.1002/jmri.24208
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive exposure of mice to strong static magnetic fields in utero does not impair fertility in adulthood but may affect placental weight of offspring

Abstract: Repetitive in utero exposure to strong static magnetic fields does not impair fertility but may have a parental-dependent effect on fetal programming with regard to placental development and fetal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…37 In fact, we also did some short-term behavior tests in combination with some mechanistic studies about the neural system to investigate the transient effects of these high SMF exposure, which will be reported in a separate paper later. Moreover, according to studies investigating the effects of on the skeletal, 38,39 cardiovascular, 40 and reproductive and developmental 41,42 systems, it is possible that other physiological aspects could be affected by ultra-high SMFs, which will need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…37 In fact, we also did some short-term behavior tests in combination with some mechanistic studies about the neural system to investigate the transient effects of these high SMF exposure, which will be reported in a separate paper later. Moreover, according to studies investigating the effects of on the skeletal, 38,39 cardiovascular, 40 and reproductive and developmental 41,42 systems, it is possible that other physiological aspects could be affected by ultra-high SMFs, which will need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Possible adverse effects on reproductive systems by exposure to NIR from MRI system are one of the concerning issues for female employees at MRI facility. Although there are several animal studies whose results showed no adverse effects on fetal developing processes by SMF exposure [5][6][7] or a large-scale epidemiology study which aimed to clarify the influence of fetal MRI examination and showed no harmful effects, 8 these studies do not directly lead to the answers of our concerns. Our present study implemented a questionnaire survey among female employees who worked at MRI facilities and examined the influence of occupational NIR exposure from MRI systems on delivery outcomes to supplement the lack of updated epidemiological evidence.…”
Section: Discussionmentioning
confidence: 84%
“…For example, Bekhite et al [2016] exposed pregnant mice to homogeneous 1 or 10 mT SMFs generated by electromagnets for 20 days and found that only 10 mT treatment caused fetal liver, kidney, and lung tissue damage, and affected eye development, but not the 1 mT treatment group. Zaun et al [2014] placed pregnant mice at the entrance and center of 1.5 and 7 T MRI devices, which provide inhomogeneous and homogeneous SMFs, respectively. There were no abnormalities in sperm morphology or density in all groups, though the sperm motility of offspring exposed to the entrance of 1.5 T MRI (inhomogeneous field) was decreased, but not the other groups (the center of 1.5 or 7 T).…”
Section: Factors That Contribute To the Differential Effects On Repro...mentioning
confidence: 99%
“…Most studies reported absence of SMF effects on sperm, or observed sperm alignment changes. However, there are also a few studies that reported changes [Tablado et al, 1996] or negative effects [Tablado et al, 1998;Tablado et al, 2000;Monfared et al, 2009;Zaun et al, 2014]. Moreover, most studies that showed negative effects were generated by inhomogeneous SMFs [Tablado et al, 1998[Tablado et al, , 2000Monfared et al, 2009;Zaun et al, 2014].…”
Section: The Effects Of Smfs On Male Spermmentioning
confidence: 99%